Calculation of contact transscleral diode laser cyclophotocoagulation parameters on the basis of ciliary body original state assessment using ultrasound biomicroscopy in terminal glaucoma patients - Je. V. Egorova; A. A. Drobnica; A. N. Bessarabov (Oftalʹmologiâ, 2014)
Aim. To analyze the initial atrophy of ciliary body in patients with painful terminal glaucoma using ultrasound biomicroscopy (UBM) and the progression of ciliary body atrophy following transscleral diode laser cyclophotocoagulation (TSCPC) considering total laser energy used.Materials and methods. 56 patients (92 eyes) with terminal painful glaucoma were examined. In these patients, TSCPC with total laser energy ranged from 43.2 to 86.4 mJ was performed. Total laser energy parameters for TSCPC were determined according to the presence and degree of ciliary body atrophy of the affected eye as compared withhealthy one. Additionally, 5 terminal glaucoma eyes with clinically apparent eye globe sub-atrophy following previous TSCPC with total laser energy above the level used in this study were examined.Results. In all terminal glaucoma patients, various degrees of ciliary body atrophy was revealed using UBM. This atrophy was diagnosed by ciliary body thinning as compared with healthy eye by 28.37 %. Post-op reaction degree following TSCPC depends on total laser energy. Total laser energy parameters selection depending on initial ciliarybody atrophy reduces pain syndrome, minimizes post-op complications, prevents further ciliary body atrophy progression and decrease IOP to sub-compensated level.Conclusion. Mathematical analysis of ciliary body thickness changes depending on laser energy used was assumed as a basis of nomogram construction that provides individual calculation of maximum allowable and minimally required total laser energy.